1997
DOI: 10.1038/sj.ijo.0800478
|View full text |Cite
|
Sign up to set email alerts
|

Parity-associated weight gain and its modification by sociodemographic and behavioral factors: a prospective analysis in US women

Abstract: OBJECTIVE: To examine how the relationship between parity increase and weight gain is modi®ed by sociodemographic and behavioral factors. DESIGN: Prospective longitudinal data from the ®rst National Health and Nutrition Examination Survey (NHANES I, 1971±75) and its follow-up of those aged 25 y and older, the NHANES I Epidemiologic Follow-up Survey (NHEFS, 1982± 84). SUBJECTS: The analytical sample was nationally representative of the United States and included 2952 white or African-American non-pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 14 publications
6
61
0
3
Order By: Relevance
“…In the NHEFS, Wolfe et al found that parity-associated weight gain varied by baseline weight; white women weighing above 200 lbs at baseline had the largest weight gains for one or more births vs none. 32 Higher excess weight gains after a first birth among overweight women in our study is also consistent with pregnancy cohort studies reporting higher postpartum weight gain or retention among overweight compared to normal weight women. 8,[13][14][15][16][17][18]33 Since these studies lacked nongravid/nonparous comparison groups, it has been unclear whether higher weight retention in over- weight women is related to their own pregravid weight gain trajectory vs pregnancy or its aftermath.…”
Section: Discussionsupporting
confidence: 81%
“…In the NHEFS, Wolfe et al found that parity-associated weight gain varied by baseline weight; white women weighing above 200 lbs at baseline had the largest weight gains for one or more births vs none. 32 Higher excess weight gains after a first birth among overweight women in our study is also consistent with pregnancy cohort studies reporting higher postpartum weight gain or retention among overweight compared to normal weight women. 8,[13][14][15][16][17][18]33 Since these studies lacked nongravid/nonparous comparison groups, it has been unclear whether higher weight retention in over- weight women is related to their own pregravid weight gain trajectory vs pregnancy or its aftermath.…”
Section: Discussionsupporting
confidence: 81%
“…9 Thus, there has been an increasing interest in investigating risk factors associated with obesity and weight gain over time. It has been reported that certain hereditary factors, 10,11 energy intake, 12,13 certain demographic, sociocultural, behavioral, and reproductive factors [13][14][15][16] are associated with obesity and weight gain, yet the findings are far from conclusive. The findings from different studies differ in magnitude and even in direction.…”
Section: Introductionmentioning
confidence: 82%
“…1 Despite public awareness of the health risks of obesity, unhealthy weight gain is common in Australian adults. 2 One group at particular risk is women of child-bearing age (18-45 years), [2][3][4] particularly those with children, who are not only at high risk of weight gain due to pregnancy, [5][6][7][8] but experience a high risk of physical inactivity, 9 unhealthy eating patterns 10 and the greatest barriers to adopting healthy lifestyle changes. 11 Women with children who live in socioeconomically disadvantaged neighbourhoods face even greater risk of obesity, as evidence suggests that neighbourhood deprivation is associated with obesity risk, independently of individual-level socioeconomic position.…”
Section: Introductionmentioning
confidence: 99%